Career expectations and influences of emerging dental workforce: A quantitative study of final year dental students in Malaysia - Che Musa, Muhd Firdaus; Gallagher, Jennifer E.; Bernabe, Eduardo (2015)
Malaysia has experienced a rapid expansion in the number of dental schools. Five factors have influenced their choice of professional career, with ‘academic’ factor being the most important. Research into the career expectations of emerging graduates is important to inform career planning and workforce retention. The objective of this study was to explore short and long-term career expectations, and influences, in relation to individual and school characteristics.